Frequency of detection of Gardnerella vaginalis in vaginal smears in the Upper Carniola region - Grmek-Košnik, Irena (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2016)
Introduction: Bacterial vaginosis is of clinical interest because of its possible causal relationship with complications during pregnancy, postpartum, and complications after surgery. Methods: Gram stain for clue cells and Gardnerella vaginalis culture methods were evaluated retrospectively in a microbiological medical laboratory for the first half of 2015. We were interested in the proportion of G. vaginalis bacteria isolated from genital samples, correlation with Gram-staining presence of clue cells, referral clinical diagnosis, and pregnancy. Results: In the first half of 2015 we received 358 vaginal specimens; 82% of them had a referral clinical diagnosis of colpitis, cervicitis, or vaginal discharge; 40% were pregnant women. G. vaginalis was isolated from 14% of vaginal specimens, and 52% of these came from pregnant patients. Gram stain clue cells and isolation of G. vaginalis matched in 86%. Conclusion: For diagnosing bacterial vaginosis in clinical practice, standard clinical criteria, Gram staining of vaginal discharge smear, and/or isolation of G. vaginalis are used. Isolation of G. vaginalis without clue cells is reported only in cases in which bacterial growth is predominant. The results of our studies confirm that isolating G. vaginalis helps confirm the diagnosis of bacterial vaginosis.
Keywords: bacterial vaginosis; bakterijska vaginoza; Gardnerella vaginalis; vaginal smears; vaginalni brisi